Hubungan Media Sosial TikTok Terhadap Kemampuan Komunikasi Matematis Siswa - Prasetyo, Agung Dwi; Firmansyah, Dani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Social media TikTok is a digital platform that is popular among teenagers and young people, often used as a medium for mathematical learning. TikTok is a platform for them to present short explanatory videos on various mathematical topics, facilitating creative and interactive mathematical communication. Although TikTok is generally known as a means of entertainment, its potential use in the context of mathematics education has not been widely explored. This research explores the relationship between junior high school students' interactions with TikTok as a mathematics learning medium and its impact on their mathematical communication skills. Through a quantitative approach with correlational research methods, data was collected through questionnaires and mathematical communication ability tests. Class VIII 2 was selected as a sample through a simple random sampling technique in the Bekasi area. The results of the analysis using Spearman's Rank correlation show that, although TikTok is often used as a mathematics learning medium, junior high school students' mathematical communication skills tend to be low or even insignificant..Â Media sosial sosial TikTok merupakan sebuah platform digital yang terkenal di kalangan remaja dan kaum muda, seringkali digunakan sebagai media pembelajaran matematis. TikTok menjadi wadah bagi mereka untuk menyajikan video penjelasan singkat mengenai berbagai topik materi matematika, memfasilitasi komunikasi matematis yang kreatif dan interaktif. Meskipun TikTok pada umumnya dikenal sebagai sarana hiburan, potensi pemanfaatannya dalam konteks pendidikan matematika masih belum banyak dieksplorasi. Penelitian ini difokuskan pada penyelidikan hubungan antara interaksi siswa SMP dengan TikTok sebagai media pembelajaran matematika dan dampaknya terhadap kemampuan komunikasi matematis mereka. Melalui pendekatan kuantitatif dengan metode penelitian korelasional, data dikumpulkan melalui kuesioner angket dan tes kemampuan komunikasi matematis. Kelas VIII 2 dipilih sebagai sampel melalui teknik pengambilan sampel acak sederhana di sebuah daerah Bekasi. Hasil analisis menggunakan korelasi Rank Spearman menunjukkan bahwa, meskipun TikTok sering digunakan sebagai media pembelajaran matematis hubungannya dengan kemampuan komunikasi matematis siswa SMP cenderung rendah atau bahkan tidak signifikan.